The impact of blended-ESP instructional model on fostering English proficiency among students majoring in traditional Chinese medicine - Ruirui Yu; Wilawan Champakaew (English Language Teaching Educational Journal)
English proficiency is essential for traditional Chinese medicine (TCM) majors to maintain strong connections with the international academic community and promote global academic interaction. However, the English instruction effect was not optimal due to large class sizes, limited class time and learning resources, less interaction, or outdated teaching and evaluation methods (Wang, 2016; Ren, 2017; Chen & Liang, 2020; Liu, 2022). This study aimed to investigate the impact of the blended-ESP instructional model (BEIM) on fostering students’ English proficiency as well as explore their attitudes and perspectives on the implementation of BEIM. The participants were 73 second-year TCM majors enrolled in the TCM English course at a TCM university in China. The instruments were pre- and post-tests, a questionnaire, and an interview. The data was analyzed using mean, standard deviation, paired t-test, segmented analysis, and thematic analysis. The results demonstrated the effectiveness of BEIM on fostering students’ English proficiency for the significant differences between the scores before and after implementing BEIM at 0.000 (P= 0.000). The results of the questionnaire and interview also revealed students’ positive attitudes and perspectives on BEIM. Students’ self-disciplinary, English proficiency, and national culture awareness and confidence should be highlighted when conducting blended-ESP instruction.